2012
DOI: 10.1371/journal.pone.0038631
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Epithelial Cell Transplantation Induces Markers of Alternative Macrophage Activation and Reduces Established Hepatic Fibrosis

Abstract: Chronic hepatic inflammation from multiple etiologies leads to a fibrogenic response that can progress to cirrhosis and liver failure. Transplantation of human amniotic epithelial cells (hAEC) from term delivered placenta has been shown to decrease mild to moderate hepatic fibrosis in a murine model. To model advanced human liver disease and assess the efficacy of hAEC therapy, we transplanted hAEC in mice with advanced hepatic fibrosis. Immunocompetent C57BL/6 mice were administered carbon tetrachloride (CCl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
114
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(132 citation statements)
references
References 43 publications
12
114
0
2
Order By: Relevance
“…This could be due to the previously described epithelial-to-mesenchymal cell transition that amniotic epithelial cells undergo after various passages in culture (37). Both in vitro and in vivo studies have demonstrated that cells from either the epithelial or mesenchymal layers exert immunomodulatory properties and ameliorate disease with inflammatory bases, including lung and liver fibrosis and EAE (15,19,(38)(39)(40)(41). Interestingly, an important percentage of the HAMCs used in our study expressed CD106 (vascular cell adhesion molecule 1), which identifies a subpopulation of mesenchymal stem cells with unique immunoregulatory properties in various tissues, especially in the placenta (42).…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the previously described epithelial-to-mesenchymal cell transition that amniotic epithelial cells undergo after various passages in culture (37). Both in vitro and in vivo studies have demonstrated that cells from either the epithelial or mesenchymal layers exert immunomodulatory properties and ameliorate disease with inflammatory bases, including lung and liver fibrosis and EAE (15,19,(38)(39)(40)(41). Interestingly, an important percentage of the HAMCs used in our study expressed CD106 (vascular cell adhesion molecule 1), which identifies a subpopulation of mesenchymal stem cells with unique immunoregulatory properties in various tissues, especially in the placenta (42).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the xenogeneic conditions (human-rat), the human amnion membrane patch modulated the severity and progression of fibrosis. Manuelpillai et al demonstrated that systemic hAEC transplantation improved carbon tetrachloride-induced mouse liver fibrosis [55,56]. The xenogeneic (human-mouse) cell transplantation induced a significant reduction of activated hepatic stellate cells in the host liver.…”
Section: Liver Fibrosismentioning
confidence: 99%
“…The mechanisms implicated in the immunosuppressive and immunomodulatory properties of AECs have been elucidated using various target cells of the innate and the adaptive immune systems. AECs inhibit alloreactive T-lymphocytes in a mixed lymphocyte reaction (Pianta et al, 2015) and they also foster the switch from T-helper (Th) 1 and Th17 lymphocytes, to Th2 and Treg (Pianta et al, 2015), and M1 to M2 macrophages (Manuelpillai et al, 2012) through the release of anti-inflammatory cytokines. AECs also block maturation of monocytes into dendritic cells (Magatti et al, 2009) and inhibit proliferation of activated peripheral blood mononuclear cells in vitro (Wolbank et al, 2007) partly through the secretion of anti-inflammatory cytokines (Kang J. W. et al, 2012).…”
Section: Combat Inflammagingmentioning
confidence: 99%
“…Sustained hepatic inflammation is a key prerequisite for fibrogenesis and is characterized by an activation of fibrogenic hepatic stellate cells and macrophages, both of which being reverted by the treatment with AECs (Manuelpillai et al, 2012; Hodge et al, 2014). The anti-fibrotic activity of transplanted AECs is accompanied by a reduction in hepatic TNF-α, IL-6, and TGF-β levels, and an induction in IL-10 levels and metalloproteinase-2 activity (Manuelpillai et al, 2010).…”
Section: Combat Inflammagingmentioning
confidence: 99%